Carbonation of cement paste with GGBFS: Effect of curing duration, replacement level and CO2 concentration on the reaction products and CO2 buffer capacity. (May 2022) - Vanoutrive, Hanne; Minne, Peter; Van de Voorde, Ilse; Cizer, Özlem; Gruyaert, Elke
Abstract: Uncertainties related to durability of concrete arise when Portland Cement (PC) is combined with supplementary cementitious materials, urging a more thorough understanding of the deterioration mechanisms. This paper focusses on carbonation, specifically the effect of replacement level of PC by ground granulated blast-furnace slag (GGBFS), curing duration and CO 2 concentration on the reaction products and CO 2 buffer capacity. The experimental test program included the determination of the hydration degree of PC, the reaction degree of GGBFS and an analysis of the reaction products by Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) spectroscopy. ATR-FTIR spectra of cement paste powders showed a delay in calcium silicate hydrate (C-S-H) decalcification upon carbonation in case of 40wt% GGBFS by increasing the curing period from 3 to 7 and 28 days. However for 70wt% GGBFS, C-S-H decalcification was quick and irrespective of the curing period whereas in neat PC, C-S-H decalcification was minimal. When comparing elevated and natural CO 2 concentrations, portlandite contents and the formed CaCO 3 polymorphs were comparable while the carbonate content and C-S-H decalcification lack resemblance suggesting different carbonation stages. ATR-FTIR spectra from the exposed surface towards the centre showed a systematic agreement between the peak area of carbonates and the colour change boundary by phenolphthalein. The spectra also suggested the transformation of aragonite to calcite during ongoing carbonation of mixes with 70wt% GGBFS and 40wt% GGBFS cured for 3 days. The use of phenolphthalein to distinguish carbonation does not reflect the heterogeneous composition of the microstructure of (partially) carbonated areas.